A Smart Home Automation system using IoT and Open Source Hardware - S.S. Tejesh, B; Neeraja, S (International Journal of Engineering and Technology, 2018)
In the era of Internet of Things, the information will be exchanged without the intervention of human. The manual systems are transforming into smart systems with the incorporation of IoT. The remote superintendence of electrical devices and sensors in the home environment with the employment of the internet is called as home automation. The electrical devices like bulb, fan and the sensors like temperature sensor, gas sensor, flame sensor, PIR sensor, current sensor are monitored and controlled by the user remotely with the employment of IoT technology. The implemented system, has both the transmitter and receiver section. In the transmitter section the information from room 1 and room 2 will be gathered at the central server. The Arduino Uno and ESP8266 plays a significant role in the transmitter section. The Raspberry Pi central server facilitates the gathered information to the user in a Graphical user interface.Â